LEUKOCYTES DIFFERENTIATION OF Pangasius hypopthalmus FED WITH TURMERIC (Curcuma domestica V) - Sari, Nur Maya; Riauwaty, Morina; Lukistyowati, Iesje (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted on September until November 2017 in Parasites and Fish Diseases Laboratory, Faculty of Fisheries and Marine Science, University of Riau, Pekanbaru. The aim of this research is to know the effect of  turmeric (Curcuma domestica V) supplementation on  total leukocytes andleukocytes differentiation of Pangasius hypophthalmus.This research used Pangasius hypopthalmus size 8-12 cm with stocking densities 50/cages. The method used was an experiment method with a Completely Randomized Design (CRD), one factor with four treatments, namely P0 (feed without turmeric), P1(feed with turmeric of 0,5 g/kg), P2(feed with turmeric of 0,7 g/kg), P3(feed with turmeric of 0,9 g/kg). The results shown the turmericduring 60 days of maintenance has effect (P<0,05) to thetotal leucocyte and lymphocyte. The best treatment of  P2 (dose 0,7 g/kg).With total leucocyte 10,21 x 104 sel/mm3, lymphocytes 83,66%, neutrophils 6,66%, monocyte 9,66%,, survival rate 92%, and ), absolute weight equal 40,86 g. It can be concluded that the use of turmeric can increase the immune system of the Pangasius hypopthalmus.Keywords:Pangasius hypopthalmus,Curcuma domestica V, Leucocytes,lymphocyte